Draft Annual Plan 2010-2011 Volume-II A (Statistical Tables) - Planning Commission (Planning Commission, 2010)
Proposed Outlays - Major Heads / Minor Heads of Development A Proposed Outlay on Continuing and New Schemes Proposed Outlay on Continuing and New Schemes.
(Statistical Tables)